HUBUNGAN MOTIVASI DAN PENGETAHUAN TERHADAP PELAKSANAAN MOBILISASI DINI PADA PASIEN POST OPERASI FRAKTUR EKSTRESMITAS BAWAH DI RUANG EDELWEIS RSUD ARIFIN ACHMAD - Pito Pirnanda; Muhammad Irwan; Erika Erika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
According to the World Health Organization (WHO), the incidence of fractures will increase worldwide by 2020, with a prevalence rate of 2.7%. By 2022, the prevalence of lower extremity fractures will increase by 3.2%, or approximately 15 million people will experience a lower extremity fracture each year. The purpose of this study was to determine the relationship between motivation and knowledge on the implementation of early mobilization in postoperative patients with lower extremity fractures in the Edelweiss Room of Arifin Achmad Hospital, Riau Province. The type of research that will be used in this study is quantitative research using descriptive correlation with